Physical activity of older schoolchildren, 11-18 years old, in the city of Manila (Journal of the Nutritionist-Dieticians' Association of the Philippines, 2006)
The study aimed at assessing the physical activity of older school children using a structured self-administered questionnaire to assist planners in formulating policies and programs that will help children be more physically active than they are presently. The study included 1,212 children, 11-18 years old, selected on the levels of physical activities (light, moderate, and vigorous) on a Physical Education (PE) day, non-PE-day, and a weekend. A scoring system to determine the physical activity levels was used. There was twice as much female (N=815) than the male students (N=402) in the study. Results revealed significant increasing "inactivity" among the students as they move up to the highest academic level. Overall, majority of the students (86%) were inactive in both public and private schools. In all the 3 days of records, the highest frequency of physical activity was recorded for "watching television" and light activities, i.e., playing video or just sitting down or talking with friends at school after lunch. Three out of 10 did not do sports during the weekends. Fourteen percent (14%) of the subjects shared common moderate activities such as walking or exercise, playing basketball and volleyball, and jogging and running, which were mostly done in school. Thus to help children become more physically active, health-related physical activity programs must be introduced and implemented at a young age to ensure early formation of appropriate physical activity habits.